Penyuluhan Pendampingan MULA (Muhibbul Lughoh Al-Arabiyah) pada Mahasiswa IAI Nusantara Ash-Shiddiqiyah Lempuing Jaya, OKI - Roziqin, Achmad; Ni'mah, Isnaini Khoirotun; Amelina, Rista (Nawadeepa: Jurnal Pengabdian Masyarakat, 2023)
Learning Arabic is something that is closely related to students at Islamic Religious Colleges. The reality is that there are several students who are interested in learning Arabic. At IAI Nusantara Ash-Shiddiqiyah for students who have an inclination towards the Arabic language are organized in the MULA (Muhibbul Lughoh Al-Arabiyah) program. The assistance provided by the community service team is focused on learning Arabic in terms of vocabulary mastery and conversation. The method used in this service is Service Learning using (four) 4 stages: planning, implementation, evaluation and improvement. The result of this mentoring is an increase in students' vocabulary and an increase in the ability to communicate using Arabic.